Конституціоналістика у складі юридичних терміно-понять - Орзіх, Марко Пилипович; Орзих, Марк Филиппович; Orzih, Mark (My University, 2009)
The c o n s t i t u t i o n a l activity is usually defined with t h e traditional categories. It t h e article a u t h o r s t a t e s , t h a t t h e r e is t h e n e c e s s i t y of an i n t r o d u c t i o n of a n e w t e r m — «constitutionalistics». This t e r m has an integrative n a t u r e and is proposed on the basis of differentiation between the subject of the science and the object of the science.
Орзіх М. П. Конституціоналістика у складі юридичних терміно-понять / М. П. Орзіх // Наукові праці Одеської національної юридичної академії / голов. ред. С. В. Ківалов ; МОН України, ОНЮА. - Одеса : Юрид. л-ра, 2009. - Т. 8. - С. 118-124.
Keywords: конституціоналістика; категорія; об'єкт науки; конституционалистика; категория; объект науки; constutionalistics; category; sciense subject